Anita Schottische (W. H. Oakes, ca. 1856) - Ferrer, Manuel; PETTINOS, George F. (R. Stevenson, Los Angeles (California), 1986)
RESUMEN: Partitura de Manuel Y. Ferrer, arreglo para piano de George F. Pettinos